Increasing incidence of paediatric inflammatory bowel disease in Ontario, Canada: evidence from health administrative data. Issue 11 (2nd August 2009) - Benchimol, E I; Guttmann, A; Griffiths, A M; Rabeneck, L; Mack, D R; Brill, H; Howard, J; Guan, J; To, T
Abstract : Objective: Health administrative databases can be used to track chronic diseases. The aim of this study was to validate a case ascertainment definition of paediatric-onset inflammatory bowel disease (IBD) using administrative data and describe its epidemiology in Ontario, Canada. Methods: A population-based clinical database of patients with IBD aged <15 years was used to define cases, and patient information was linked to health administrative data to compare the accuracy of various patterns of healthcare use. The most accurate algorithm was validated with chart data of children aged <18 years from 12 medical practices. Administrative data from the period 1991–2008 were used to describe the incidence and prevalence of IBD in Ontario children. Changes in incidence were tested using Poisson regression. Results: Accurate identification of children with IBD required four physician contacts or two hospitalisations (with International Classification of Disease (ICD) codes for IBD) within 3 years if they underwent colonoscopy and seven contacts or three hospitalisations within 3 years in those without colonoscopy (children <12 years old, sensitivity 90.5%, specificity >99.9%; children <15 years old, sensitivity 89.6%, specificity >99.9%; children <18 years old, sensitivity 91.1%, specificity 99.5%). Age- and sex-standardised prevalence per 100 000 population of paediatric IBD has increased from 42.1 (in 1994) to 56.3 (in 2005). Incidence per 100 000 has increased from 9.5 (in 1994) to 11.4 (in 2005). Statistically significant increases in incidence were noted in 0–4 year olds (5.0%/year, p = 0.03) and 5–9 year olds (7.6%/year, p<0.0001), but not in 10–14 or 15–17 year olds. Conclusion: Ontario has one of the highest rates of childhood-onset IBD in the world, and there is an accelerated increase in incidence in younger children.